2016
DOI: 10.1016/j.csda.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian crossover designs for generalized linear models

Abstract: This article discusses D-optimal Bayesian crossover designs for generalized linear models.Crossover trials with t treatments and p periods, for t <= p, are considered. The designs proposed in this paper minimize the log determinant of the variance of the estimated treatment effects over all possible allocation of the n subjects to the treatment sequences. It is assumed that the p observations from each subject are mutually correlated while the observations from different subjects are uncorrelated. Since main i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…where W j = Cov(Y j ). As mentioned by Singh and Mukhopadhyay (2016) in the paper (Zeger et al, 1988, equation (3.2)) it has also been shown that if the true correlation structure varies from "working correlation" structure, then Var(θ) is given by the sandwich formula…”
Section: Generalized Estimating Equationsmentioning
confidence: 96%
“…where W j = Cov(Y j ). As mentioned by Singh and Mukhopadhyay (2016) in the paper (Zeger et al, 1988, equation (3.2)) it has also been shown that if the true correlation structure varies from "working correlation" structure, then Var(θ) is given by the sandwich formula…”
Section: Generalized Estimating Equationsmentioning
confidence: 96%
“…A pseudo‐Bayesian approach was adopted by Woods and Van de Ven (2011) in the context of block designs for nonnormal responses, Singh and Mukhopadhyay (2016a) for cluster designs, Singh and Mukhopadhyay (2016b) for crossover designs, Singh and Davidov (2020) for multiple comparison problems, and Singh et al. (2021) for binary cluster designs.…”
Section: Bayesian Designmentioning
confidence: 99%
“…Then for the misspecified models, we regard the estimators as the single prior to select locally general optimal design do,misjL, or construct the prior space based on the estimators and select the Bayesian general optimal design do,misjB,j= 4, …, 11. After obtaining these designs, similar to Singh and Mukhopadhyay (2016), we compare the REs of them relative to doL under boldα̂o which is selected without misspecification. The results are shown in Table 3.…”
Section: Data Illustration: Cattle Datamentioning
confidence: 99%